2008
DOI: 10.1007/s11244-008-9109-9
|View full text |Cite
|
Sign up to set email alerts
|

Steric Effect on the Catalytic Performance of the Selective Oxidation of Alcohols Over Novel Crystalline Mo–V–O Oxide

Abstract: The Mo-V-O crystalline oxide with novel pore structure and consisting uniform six-and seven-member rings on the a-b plane is investigated for the selective oxidation of alcohols of different steric hindrance in liquid phase. The research target is to correlate catalytic activity with the pore structure of the crystal. Specially, substituted pyridines are employed as probe molecules to study poison effect which is closely related to the steric hindrance. As a result, the oxidation of benzyl alcohol, 1-hexanol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…[3] These studies, which mainly focus on identifying crystalline phases employing X-ray radiation or electron emission as detection techniques, provide complex information including both the surface and bulk phase. [6] Inspired by this work, we endeavored to develop new strategies to detect and measure surface electrons, and to establish a structure-activity relationship. Calculations have proposed models of surface defect sites, and have suggested that electrons left behind after oxygen removal could be confined or be localized in defect sites or oxygen vacancy sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3] These studies, which mainly focus on identifying crystalline phases employing X-ray radiation or electron emission as detection techniques, provide complex information including both the surface and bulk phase. [6] Inspired by this work, we endeavored to develop new strategies to detect and measure surface electrons, and to establish a structure-activity relationship. Calculations have proposed models of surface defect sites, and have suggested that electrons left behind after oxygen removal could be confined or be localized in defect sites or oxygen vacancy sites.…”
mentioning
confidence: 99%
“…[4,5] We have employed probe reactions to investigate the surface properties of oxide catalysts, and have obtained precise surface information, such as acidity and basicity, at the identical level of contacted adsorbates, reactants, or sensing gas. [6] Inspired by this work, we endeavored to develop new strategies to detect and measure surface electrons, and to establish a structure-activity relationship. It turns out that confined electrons on the surface of reduced MoO x are transferrable to the pertinent environment, and such electron transfer greatly depends on the reduction degree of MoO x and the electron affinity of acceptors.…”
mentioning
confidence: 99%
“…Mixed metal oxides of Mo and V have shown much promise in this regard, but remain less active than their PGM counterparts. Wang and coworkers [111][112][113][114] recently demonstrated that crystalline Mo-V-O with an orthorhombic structure can efficiently catalyze benzyl alcohol oxidation to benzaldehyde using either dioxygen or air. Such mixed metal oxides can be reused without appreciable selectivity loss.…”
Section: Oxide Sulfide and Vanadate Catalystsmentioning
confidence: 99%
“…. Orthorhombic Mo _ V _ oxide exhibits outstanding catalytic activities for several oxidation reactions (e.g., propane oxidation 28) , acrolein oxidation 12) , and alcohol oxidation 29) with molecular oxygen) without collapse of its orthorhombic structure. This catalytic activity indicates that the orthorhombic Mo _ V _ oxide can accept and release electons, protons, and/or oxygen atoms.…”
Section: Redox-tunable Reversible Micropores In Thementioning
confidence: 99%